Ocena lesne zaloge sestojev iz podatkov zračnega laserskega skeniranja površja - Kobal, Milan (Gozdarski vestnik, 2014)
In addition to forest area, growing stock is one of the most often measured data about forests. The first data on growing stock in forests were based on the basis of ocular estimates. Nowadays statistical sampling is used. In the foreign countries, evaluation of growing stock based on airborne laser scanning and lidar data is already well established. In this paper, the possibility of such estimates of growing stock in case of uneven aged Dinaric silver fir-European beech forests is presented. Similarly as in comparable studies on the evaluation of the growing stock based on laser scanning data, we confirmed this possibility also in this study. Considering the average tree height and canopy transparency on the plot level in the model, we explained 82% of the variability of growing stock, root mean square error RMSE is 55.2 m3/ha or 8.6%.
Keywords: zračno lasersko skeniranje; airborne laser scanning; lidar; lesna zaloga; growing stock; jelovo-bukovi gozdovi